2013
DOI: 10.1007/s12178-013-9155-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of proximal humerus fractures utilizing reverse total shoulder arthroplasty

Abstract: The increased incidence of proximal humerus fractures has resulted in a thoughtful evolution of treatment options in order to optimize clinical outcomes. Complex three-and four-part fractures present a treatment challenge, particularly in elderly patients with significant medial comorbidities and poor bone quality. While open reduction and internal fixation is a reasonable surgical option in some patients with acceptable bone quality and simple fracture patterns that are not susceptible to avascular necrosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…The initial database search yielded 367 papers; 283 were excluded due to inappropriate types (e.g., abstracts, Included studies (8) Not reporting the specific therapeutic methods (56) Irrelevant population and outcomes (14) Insufficient quantitative data (6) reduplicative, letters and meeting reports); 56 were excluded for not meeting the specific therapeutic methods according to criteria; 14 were excluded for reporting results of no interest; six were excluded as they did not provide sufficient data for meta-analysis. Eight studies were identified to be eligible and included in this meta-analysis.…”
Section: Research Results and Basic Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial database search yielded 367 papers; 283 were excluded due to inappropriate types (e.g., abstracts, Included studies (8) Not reporting the specific therapeutic methods (56) Irrelevant population and outcomes (14) Insufficient quantitative data (6) reduplicative, letters and meeting reports); 56 were excluded for not meeting the specific therapeutic methods according to criteria; 14 were excluded for reporting results of no interest; six were excluded as they did not provide sufficient data for meta-analysis. Eight studies were identified to be eligible and included in this meta-analysis.…”
Section: Research Results and Basic Informationmentioning
confidence: 99%
“…2a and 3a) has been labeled as the Bgold standard^for complex proximal humerus fractures, with lower incidence of complication and improved function. However, the advantages are generally compromised by poor tuberosity healing, osteolysis of the tuberosities and subsequent loss of function, documented in literature [8][9][10][11]. RSA (Figs.…”
Section: Introductionmentioning
confidence: 99%
“…For hemiarthroplasties, this dislocation rate has been attributed to failure of the greater tuberosity repair and was reported to be as much as 14% [13]. This led to the introduction of reverse total shoulder arthroplasty for the treatment of proximal humerus fractures with significant comminution of the greater tuberosity [23,28]. The frequency of reverse total shoulder arthroplasty dislocations has been variable, ranging from 2.3% in patients with proximal humerus fractures [4] to 30.8% in patients after tumor resection [9].…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates have been reported as high with open reduction and internal fixation (ORIF) despite technologic improvements such as locked plating [14,17,18,25,31]. Although surgeons now are using hemiarthroplasty of the humeral head and reverse total shoulder replacement in an attempt to improve functional outcomes after treatment of comminuted three-or four-part fractures and fractures that have a head-split component [3,6,10,15,23], these arthroplasty techniques for fracture care also have associated complications [3,39].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have indicated that tuberosity healing portends superior results, it is not a prerequisite to good functional outcomes in patients undergoing rTSA. [1,48,55,62] Therefore, it has been postulated that in patients such as elderly patients and those with complex fractures of the proximal humerus who may be predisposed to fracture nonunion/malunion or ORIF is not feasible, rTSA may be a better option than HA.…”
Section: Rtsa For Fractures Of the Proximal Humerusmentioning
confidence: 99%